Fluorescence-Guided Identification of the Thoracic Duct by VATS for Treatment of Postoperative Chylothorax: A Short Case Series - Londero, Francesco; Grossi, William; Vecchiato, Massimo; Martino, Antonio; Ziccarelli, Antonio; Petri, Roberto; Morelli, Angelo (Frontiers in Surgery, 2022)
Background: Chylothorax is a relatively rare complication after surgery of the mediastinum. The occurrence and the results of surgical treatment of this condition are difficult to foresee, due to the wide heterogeneity in thoracic duct anatomy. Case Summary: We report two cases of post-operative chylothorax treated with ligation by VATS. The first patient developed a massive left chylothorax shortly after discharge, following radical excision of a seminoma-involved left para-aortic lymphadenopathy. The second patient developed a high-output right chylothorax following VATS upper bilobectomy. In both cases a surgical revision by VATS was performed. Inguinal injection of indocyanine green allowed an easy visualization of the lymphatic leakage point. In both cases oral feeding was rapidly restarted after surgery. No recurrence of chylothorax was observed. Conclusion: The use of indocyanine green may greatly improve the identification of the thoracic duct during surgical ligation by VATS, with a favourable impact on the post-operative course and overall admission costs.